IMPACT OF CORPORATE GOVERNANCE & AUDIT QUALITY ON FIRMS FINANCIAL INFORMANTIONS - Khan, Sajjad Ali; Din, Dr. Sirajud; Joseph, Victoria (The journal of contemporary issues in business and government, 2022)
The aim of this research paper is to find how and when Corporate Governance and Audit Quality may control the impact of Financial Market Crises Risk on firms Financial Information through the mediator Financial Leverage. Three fundamental theories were used for the research i.e. Financial Market Theory, Corporate Governance Theory and Audit Quality Theory. The impact was tested through the Mediation Model# 4 of SPSS Hayes Process Regression Analysis. The Sample Size of 363 observations was taken from the Karachi Stock Exchange enlisted companies for the period of 2005 to 2015. The companies were rankedfor quantification after studying and analyzing the performance of the companies in their published Financial Statements. The outcome of the testing model showed that both the Independent Variables i.e. Corporate Governance and Audit Quality have normal effect on the Firms Financial Information jointly. It was found that Mediation effect exists between the relationship of Corporate Governance, Audit Quality and Financial Information as the p-value is significant which means that Corporate Governance and Audit Quality can minimize or control the effect of Financial Market Crises Risk on the dependent variable Financial Information through the mediator Financial Leverage. The practical application of the research will equip all the stakeholders about the significance of the Audit Quality and Corporate Governance impact on firm Financial Information.The stakeholders can utilize this mechanism of both Independent Variables Corporate Governance and Audit Quality separately for minimizingFinancialMarket Crises Risk.